The future of cyber security and security innovation. (O'Reilly Media, 2015)
"Now that an industry of social network manipulation has risen, phenomena like the Arab Spring are likely a thing of the past. That's part of what you'll learn with this complete video compilation of Suits and Spooks 2015 in Washington, D.C., the unique technology event that helps unmask the cold realities of cyber conflict, espionage, and crime. You'll be able to catch many of the eyebrow-raising sessions from the February 2015 conference. Taia Global's Suits and Spooks Collision event brings individuals from the U.S. Intelligence Community together with innovators and executives from a wide variety of private sector disciplines, including technology, finance, entertainment, and science. The result is two days of frank discussions, challenging perspectives, and collaborative problem solving."--Resource description page.